New Insight into the Composition and Structure of Sizing Agent from NMR Spectroscopy - Indra Neel Pulidindi (International Journal of Photochemistry and Photochemical Research, 2024)
Sized carbon fibers (CFs) are of commercial significance as they form the main load-bearing component in advanced materials, namely, carbon fiber-reinforced plastics (CFRPs). Much of the knowledge of sizing composition and the process of sizing is a subject of intellectual property rights owing to its commercial relevance. In this original research article, deeper insights into the structure and composition of the sizing agent used for the surface modification of commercial carbon fibers (NX90, NX100, CFF800, T800HB, T700SC, and M55J) were obtained using 1H, 13C, 29Si, and heteronuclear single quantum coherence (HSQC) NMR spectroscopic analysis. NMR analysis of the sizing compound extracted from the sized carbon fibers revealed that indeed a dimer of diglycidyl ether of bisphenol A, DGEBA, (trade name, E51) is used in the sizing composition for making the fiber compatible with the polymer matrices to increase the interfacial strength via improved chemical bonding.
Keywords: CFF800; CFRPs; Carbon fibers; DGEBA dimer; E51; HDMS; M55J; NX100; NX90; PDMS; Sizing agent; T700SC; T800HB; carbon fiber reinforced plastics; crown ethers; organic siloxanes